Principles of analytical chemistry a textbook - Valcárcel Cases, Miguel (Springer, 2000)
"Principles of Analytical Chemistry aims to ease the first contact of students pursuing differnt scientific and technical studies by providing them with a simple, general overview of the discipline. The objective of this innovative textbook is to teach rather than to inform. Using keywords of modern Analytical Chemistry, it constructs a teaching message accessible to the teaching contents of the book. Practical exercises, 450 questions for students, and 27 interactive seminars are used as vehicles for expounding a large number of examples in order to clarify and consolidate the text and facilitate its comprehension."--